The impact of CEO overconfidence on firm innovation performance and the moderating effect of firm specific factors within the pharmaceutical industry - Kloosterman, Sander (2019)
The influence of overconfident CEOs on their firms, and more particularly the level of innovativeness of the firm is gaining more attention in the current complex business environment. In addition, the ways in which CEO personality traits influence organisational outcomes are of interest to several disciplines, as is reflected in the research available. Using several regression models, this thesis examines the moderating impact of three firm-specific factors (organisational slack, firm leverage and firm growth) on the relationship between CEO overconfidence and firm innovation performance. The study includes data from 2011-2016 of 85 different firms within the global pharmaceutical industry, resulting in 479 firm year observations. Results show that the initial positive relationship between CEO overconfidence and firm innovation performance is not supported (H1). Despite this insignificant outcome, the findings suggest a positive moderating effect of organisational slack (H2) on the relationship between CEO overconfidence and firm innovation performance. No moderating effect could be established for firm leverage (H3) or firm growth (H4) on the relationship between CEO overconfidence and firm innovation performance, preventing us from drawing any further inferences. Based on this research, firms are recommended to set sensible targets for organisational slack as this allows for appropriate funding of innovative projects which can have both significant direct and indirect effects on the innovation performance of a firm.